PROSPECTS OF THE DNIESTER RIVER FLOODPLAIN TERRACES STRATA FOR GOLD MINERALIZATION - Derevska, K.; Aleksandrov, O.; Berehovenko, V.; Kovalchuk, M.; Rudenko, K.; Silchenko, G.; Spytsia, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Despite long-term geological study of the Dniester River basin, we still have no clear evidences about gold-bearing potentiality of this area as well as origin of gold. The leading role of geological, geochemical and mineralogical criteria is proved for defining the prospects of substantial gold deposits finding within the Dniester river basin. Gold was found here in the crystalline basement and in the sedimentary cover rocks. Study of mineralogy and lithology of the terraces above the flood-plain and typomorphic peculiarities of native gold shows that palaeogeographic conditions and alimentation zones of debris vary at the different tectonic stages of this area development. Gold-bearing potential of the Pliocene-Quaternary sediments in the Dniester River basin is related to the Pliocene (VI-IX terraces above the flood-plain) and Quaternary (I-V terraces above the flood-plain) terraces complex of the Dniester river, as well as this river and its inflows recent alluvia. Our study of the Mid-flow part of the Dniester river basin allow to conclude that native gold was found in geological strata of all ages, from Proterozoic up to the recent alluvium. This fact points the necessity of further prospecting to find the mother lodes of gold. Our field study, samples analyses made as well as publications observation allow highlighting the principal directions of further prospecting and evaluation works. The main among that are: 1) comprehensive study of river Dniester alluvia and its terraces complex (previously VI–VII terraces), that will allow to specify their material composition, to assess real gold-bearing potential and to define the history of denudation areas changes; 2) lithogeochemical prospecting of primary and secondary dispersion haloes to clear the principal gold-bearing regularities; 3) definition of prospect plots within the area described; 4) modern analytical approach study of typomorphic peculiarities of native gold from alluvia and terrace deposits to define its ore formational affinity and mineral type.